2012
DOI: 10.4103/0972-2327.100031
|View full text |Cite
|
Sign up to set email alerts
|

Primary headaches in restless legs syndrome patients

Abstract: Earlier studies conducted among migraineurs have shown an association between migraine and restless legs syndrome (RLS). We chose RLS patients and looked for migraine to exclude sample bias.Materials and Methods:99 consecutive subjects of idiopathic RLS were recruited from the sleep clinic during four months period. Physician diagnosis of headache and depressive disorder was made with the help of ICHD-2 and DSM-IV-TR criteria, respectively. Sleep history was gathered. Severity of RLS and insomnia was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…[1] We agree with the fact that exclusion of subjects with iron deficiency would have improved the quality of our study. To support it, they have cited a study that shows that iron deficiency might be related to menstrual migraine.…”
supporting
confidence: 69%
“…[1] We agree with the fact that exclusion of subjects with iron deficiency would have improved the quality of our study. To support it, they have cited a study that shows that iron deficiency might be related to menstrual migraine.…”
supporting
confidence: 69%
“…The prevalence of migraine‐type headache was reported to vary between 7% and 14% in many studies, although higher rates of migraine were also reported in women in a recent study from Turkey . Only 1 recent study, by Gupta et al investigating 99 patients with RLS, showed that 22.8% of this particular group had migraine‐type headache. Our results did not support higher rates of migraine‐type headache in RLS patients when compared with population‐based prevalence studies from Turkey.…”
Section: Discussionmentioning
confidence: 93%
“…Second, possibly females frequently have medical co‐morbidities, for example, hypothyroidism, which may enhance their chances to seek a medical opinion and thus increasing the chances of RLS to come to clinical attention . Third, few of the conditions that may negatively affect sleep often accompany RLS, for example, insomnia, headache and depression . Even in the absence of RLS, these conditions are more prevalent among women and hence, they could act as a link for higher prevalence of females in a clinic's samples .…”
Section: Introductionmentioning
confidence: 99%